Análisis de armónicos en la iluminación led de sistemas de alumbrado público en la ciudad de Ambato Av. Luis Aníbal Granja Sector Huachi Chico. - Murillo Andrade, Carlos David (2019)
This research was carried out on Luis Aníbal Granja Avenue related to the streetlight installed on this Avenue located in Ambato. The research purpose was to detect and correct the harmonics presence of current and voltage in LED luminaires that are currently installed, to fulfil with the limits established by national regulations CONELEC 008/11 and international standards. To know about the theme, a bibliographic and field research was carried out, which allowed to improve this research. A FLUKE 435 energy quality meter was installed in the 8 transformation chambers that supply the whole streetlight network on the avenue and the analysis of the respective measurements was carried out, detecting the current harmonics presence. With the EASY POWER assistance software, the load flow analysis was carried out to determine voltage drops, power losses, power flows, power factor and chargeability of the electrical system. In addition, a harmonic flow analysis was carried out to define the level of harmonics in the industry. Alternative solutions were considered for the reduction of harmonic pollution levels produced by the use of LED luminaires. LED luminaires advantages were also showed throught a comparison with previously installed luminaires. At the end of this research, conclusions and recommendations are added and the proposal is presented with the technical and economic evaluation.